2019
DOI: 10.1103/physrevresearch.1.033153
|View full text |Cite
|
Sign up to set email alerts
|

Electron-phonon coupling in d -electron solids: A temperature-dependent study of rutile TiO2 by first-principles theory and two-photon photoemission

Abstract: is a paradigmatic transition-metal oxide with applications in optics, electronics, photocatalysis, etc., that are subject to pervasive electron-phonon interaction. To understand how energies of its electronic bands, and in general semiconductors or metals where the frontier orbitals have a strong d-band character, depend on temperature, we perform a comprehensive theoretical and experimental study of the effects of electron-phonon (e-p) interactions. In a two-photon photoemission (2PP) spectroscopy study we ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 106 publications
(152 reference statements)
0
9
1
Order By: Relevance
“…For rutile TiO 2 , several studies of temperature effects have been reported. Shang et al examined temperature renormalization effects on the t 2g and e g bands in rutile TiO 2 using first-principles and two-photon photoemission spectroscopy measurements [28]. In another study, the elementary excitations in rutile TiO 2 showed anisotropic exciton temperature dependence due to electron-phonon interactions [29].…”
Section: Introductionmentioning
confidence: 99%
“…For rutile TiO 2 , several studies of temperature effects have been reported. Shang et al examined temperature renormalization effects on the t 2g and e g bands in rutile TiO 2 using first-principles and two-photon photoemission spectroscopy measurements [28]. In another study, the elementary excitations in rutile TiO 2 showed anisotropic exciton temperature dependence due to electron-phonon interactions [29].…”
Section: Introductionmentioning
confidence: 99%
“…The R-R110 2PPE spectrum was recorded after the sample cooled to 300 K following sample preparation (detailed in the SM [22]). Accurate monitoring of the sample temperature is important as temperature is known to affect 2PPE spectra of TiO 2 [23]. Surface O vac will readily react with residual UHV water; however, the chamber base pressure of 1×10 -10 mbar ensures the slow rate of hydroxylation within the time required to record the R-R110 spectrum in Fig.…”
mentioning
confidence: 99%
“…In most semiconductors, the valence band maximum (VBM) is formed by p-orbitals, while the conduction band minimum (CBM) consists of s-orbitals. In d-orbital-derived bands, such as the valence band and the conduction band in Co x Fe 3– x O 4 , band-energy shifts with temperature are expected, either to higher or lower energy depending on the surrounding ligand field . Thus, an emission with participation of the valence or the conduction band should show a distinct shift with temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In dorbital-derived bands, such as the valence band and the conduction band in Co x Fe 3−x O 4 , band-energy shifts with temperature are expected, either to higher or lower energy depending on the surrounding ligand field. 82 Thus, an emission with participation of the valence or the conduction band should show a distinct shift with temperature. Figure 4 summarizes the outcome of temperature-resolved PL measurements on Co 0.9 Fe 2.1 O 4 nanoparticles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%